(untitled) (Research, Society and Development, 2020)
This scientific work aimed to enter efficiently the game of chess as a teaching resource in the learning process of the Cartesian coordinate content in a class of 7th grade of elementary school, specifically in order to analyze and identify such a strategy to better learning content in the classroom. The methodology of the study was collected through a quantitative, qualitative descriptive research, the methodological procedures were developed from a systematic education in an attempt to integrate theory and practice, in the form of knowledge intervention in a public school in the city of Gravatá/PE. The results showed that the use of chess through a process of teaching and learning can promote meaningful learning, ie, the use of teaching resources is of paramount importance to establish this interaction between student / teacher for the subject with the be addressed.